Evaluation of the “license, master, doctorate” reform in medical school of University of Lomé (Togo): strengths and weaknesses - Julienne Noudé TECLESSOU; Essossinam KPELAO; Bayaki SAKA (BMC Medical Education, 2020)
Abstract Introduction The License, Master and Doctorate (LMD) reform that structured high studies in three cycles, has been instituted since the Bologna declaration in 1999. To be conformed to international standards, the LMD system has been instituted in University of Lomé in 2009 to foster pathways between medical and paramedical training. The purpose of this study was to evaluate the strengths and weaknesses of the LMD reform since its introduction in medical school of Lomé. Method It was an opinion survey conducted during four months in University of Lomé among the medical school’s teachers about strengths and weaknesses of LMD reform since its application. The strengths were defined as all facilities brought by LMD reform in organization of courses and practices, evaluations, new Information and Communication Technologies (ICTs) (internet, video projector, courses on line). The LMD weaknesses were defined as any problem that it could generate. Results Of 113 resident teachers of the medical school of Lomé, seventy-six have completed the questionnaire (67.2%). The majority of teachers (74) thought that the introduction of LMD reform will make Lomé medical school fit into international standards. The availability of the video projectors was mentioned by 90.8% of the teachers and 82.9% of them used it for teaching. Online course was not available. The main strengths of LMD were: a better evaluation system (33.3%), the organization of training in units with credit (28.6%), the usage of new ICTs (23.8%). Respondents also reported many weaknesses of LMD reform: the plethoric number of students (36.2%), the absence of an intermediate diploma and pathways between studies (29.3%). The Insufficiency of human resources and material was also mentioned. Conclusion This study highlights that LMD reform needs adaptation to local realities and improvement to ensure that students will get better training in conformity with international standards.